Impact of Personal Values on School Engagement Among Chinese Adolescents: Mediating Effects of Achievement Goals - Tingyu Gu; Xiaosong Gai (Behavioral Sciences)
Much of past research has centered on the impact of personal values on career progression. Yet, the connection between personal values and academic performance remains under-explored, especially the mechanisms through which they relate. Additionally, the relative strength of the correlation between different types of personal values and academic performance has yet to be examined. This research aimed to examine the effect of various personal values on school engagement among Chinese adolescents, as well as the role of four achievement goals as potential mediators. We surveyed 700 senior high school students from a public school in Changchun, Jilin province, China (Mage = 16.91, SDage = 0.43, 55.57% male). Participants completed the Personal Values Scale, Achievement Goal Orientation Scale, and School Engagement Scale. Materialistic values were positively correlated with performance avoidance goals, which in turn were negatively related to school engagement. In contrast, self-improvement values were positively associated with school engagement. This relationship was mediated by a higher number of mastery approach goals and fewer performance avoidance goals. Self-transcendence values were linked to an increase in mastery approach goals, which were in turn positively related to school engagement. Additionally, although both self-improvement and self-transcendence values positively correlated with adolescents’ school engagement, the correlation was stronger for self-improvement values. This study makes a unique contribution by showing that personal values are linked to school engagement through achievement goal orientations, thereby supporting and expanding the future-oriented motivation and self-regulation model. The practical value of this study lies in demonstrating that promoting self-improvement and self-transcendence values, particularly self-improvement values, fosters positive achievement goal orientations, such as mastery approach goals, which in turn enhance school engagement.